2018
DOI: 10.1007/s11524-018-0273-3
|View full text |Cite|
|
Sign up to set email alerts
|

Association between Firearm Laws and Homicide in Urban Counties

Abstract: Laws related to the sale, use, and carrying of firearms have been associated with differences in firearm homicide rates at the state level. Right-to-carry (RTC) and stand your ground (SYG) laws are associated with increases in firearm homicide; permit-to-purchase (PTP) laws and those prohibiting individuals convicted of violent misdemeanors (VM) have been associated with decreases in firearm homicide. Evidence for the effect of comprehensive background checks (CBC) not tied to PTP is inconclusive. Because fire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
61
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 16 publications
6
61
1
1
Order By: Relevance
“…Some licensing laws also require gun safety training, and a few provide officials the ability to use their discretion to deny an applicant if there is good reason to believe he or she might be dangerous (e.g., some history of violence). Rigorous studies of the impact of state CBC laws have not shown that these laws reduce homicides (Castillo‐Carniglia et al., ; Kagawa et al., ; Zeoli et al., ); however, there has been consistent evidence that licensing laws reduce homicides (Crifasi et al., ; Hasegawa, Webster, & Small, ; Rudolph, Stuart, Vernick, & Webster, ) and suicides (Crifasi, Meyers, Vernick, & Webster, ). Licensing laws could potentially suppress fatal mass shootings, but there are no rigorous studies examining this question.…”
mentioning
confidence: 99%
“…Some licensing laws also require gun safety training, and a few provide officials the ability to use their discretion to deny an applicant if there is good reason to believe he or she might be dangerous (e.g., some history of violence). Rigorous studies of the impact of state CBC laws have not shown that these laws reduce homicides (Castillo‐Carniglia et al., ; Kagawa et al., ; Zeoli et al., ); however, there has been consistent evidence that licensing laws reduce homicides (Crifasi et al., ; Hasegawa, Webster, & Small, ; Rudolph, Stuart, Vernick, & Webster, ) and suicides (Crifasi, Meyers, Vernick, & Webster, ). Licensing laws could potentially suppress fatal mass shootings, but there are no rigorous studies examining this question.…”
mentioning
confidence: 99%
“…12,14,15 Crifasi and associates studied the relationship between 5 state firearm laws and homicide rates in heavily populated US counties during the period 1984-2015. 12 They found that laws requiring a permit to purchase firearms were associated with an 11% reduction in firearm homicide in these urban counties. Right-to-carry laws, stand your ground laws, and violent misdemeanor prohibitions were associated with increases in firearm homicides of 7%, 8%, and 24%, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Most of the public health literature on homicide classifies urbanicity at the county level using coding schemes developed by CDC or US Department of Agriculture (USDA) ( Table A1; available online only). [5][6][7][8][9][10][11][12] Isserman highlights a problem (which he terms the "county trap") of classifying urbanicity based on counties because these designations capture integration rather than separation. 24 Research that uses CDC or USDA distinctions are classifying many counties as urban because they are tied to metropolitan areas even if the qualities of the areas making up the county being classified are decidedly nonurban on their own.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations